Dasar dan Tujuan Pendidikan Islam - Barni, Mahyuddin (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
Education as a well planned proccss, needs principles and objectives to be achieved. Education carried out in a certain country should be in Iinc with tlre objectives of the country. lslamic education, of course has principles and objectives in accordance with the lslamic teaching. In this paper, the writer will describe about Quranic verscs and Fladits which beconre thc principlc of lslamic education. The writer also explaining the objectives of lslamic education flom the opinion of many lslamic educational experts.